Knowledge Distillation and Transfer Learning Combined for Innovative Visualization Teaching of Non-Heritage Designs - Ahmad Nizam Othman (Tanjung Malim, 2024)
Knowledge Distillation and Transfer Learning Combined for Innovative Visualization Teaching of Non-Heritage Designs by Ahmad Nizam Othman